Retrospective Evaluation Of Joint Syndrome And Joint Disorders In Osteoarthritis (Texas Journal of Medical Science, 2024)
Retrospective assessment of clinical signs and course of the disease in patients with osteoarthritis in the sex ratio. Materials and Methods: In this scientific study, a retrospective analysis of 300 patients hospitalized in the City Clinical Hospital No. 3 from 2015 to 2019 was carried out based on medical records, with an emphasis on the analysis of the clinical course and consequences of the disease. Results: On the basis of the obtained data on x-ray images, the articular syndrome and joint structure disorders observed in patients with osteoarthritis (OA) were assessed. Conclusions: It was noted that in patients with OA, the articular syndrome was different and gender differences were found in the course of the disease.